2021
DOI: 10.18632/aging.203055
|View full text |Cite
|
Sign up to set email alerts
|

Can repeat IVF/ICSI cycles compensate for the natural decline in fertility with age? an estimate of cumulative live birth rates over multiple IVF/ICSI cycles in Chinese advanced-aged population

Abstract: In order to find out to what extent ovarian aging could be compensated by the in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatments, a total of 4102 women above the age of 35 undergoing 6489 complete cycles from 2009 to 2015 with follow-up visits until 2017 were retrospectively analyzed. Cumulative live birth rates (CLBRs) across multiple IVF/ICSI cycles were compared in the study population stratified by age and ovarian reserve (classified by the POSEIDON criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Another study showed that extending cycles of IVF increased CLBRs and the increase was most evident during the first three cycles 2 . This conclusion is similar to ours, the majority of the patients can get live birth within three cycles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study showed that extending cycles of IVF increased CLBRs and the increase was most evident during the first three cycles 2 . This conclusion is similar to ours, the majority of the patients can get live birth within three cycles.…”
Section: Discussionmentioning
confidence: 98%
“…After an initial failure, 50% of patients choose to try again. Evidence suggests that after repeated IVF/ICSI cycles, live birth might be achieved eventually for certain groups 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Age is the most important factor that determines the outcome after embryo transfer (ET), with either in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI), regardless whether fresh or frozen cycles ( 1 ). Previous studies showed that 38 years of age represent a significant turning point in the decline of cumulative live birth rate (CLBR) after IVF/ICSI-ET ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the officially implementation of the “two-child policy” in 2016, ~90 million Chinese women have been eligible to have a second child. However, 60% of these potential second-child mothers are advanced maternal age women whose age is above 35, and more than half are 40 years older ( 3 , 4 ), and those elder female subjects with reduced fertility usually ask for assistance from assisted reproductive technologies (ARTs). Correspondingly, the number of women over 35 years old undergoing in vitro fertilization /intracytoplasmic sperm injection (IVF/ICSI) treatments is growing rapidly worldwide ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%